2020
DOI: 10.1038/s41598-020-66251-y
|View full text |Cite
|
Sign up to set email alerts
|

An anticonvulsive drug, valproic acid (valproate), has effects on the biosynthesis of fatty acids and polyketides in microorganisms

Abstract: Valproic acid or valproate (VpA) is an anticonvulsive drug used for treatments of epilepsy, bipolar disorder, and migraine headaches. VpA is also an epigenetic modulator, inhibiting histone deacetylase, and it has been subjected to clinical study for cancer treatment. During the investigation of VpA on a metabolite profile in a fungus, we found that VPA has significant effects on the production of some fatty acids. Further exploration of VPA on fatty acid profiles of microorganisms, fungi, yeast, and bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…In addition to genetic influences, environmental factors can modify microbial profiles and could contribute to the etiology of complex disorders. Several medications, including the antiepileptic drug, valproate, modify gut microbial function including fatty acid production (Poolchanuan et al, 2020). It has also been shown that the risk of ASD diagnosis is increased in infants born to mothers prescribed valproate (Christensen et al, 2013).…”
Section: Factors Influencing Microbial Dysbiosis In Autismmentioning
confidence: 99%
“…In addition to genetic influences, environmental factors can modify microbial profiles and could contribute to the etiology of complex disorders. Several medications, including the antiepileptic drug, valproate, modify gut microbial function including fatty acid production (Poolchanuan et al, 2020). It has also been shown that the risk of ASD diagnosis is increased in infants born to mothers prescribed valproate (Christensen et al, 2013).…”
Section: Factors Influencing Microbial Dysbiosis In Autismmentioning
confidence: 99%
“…Naturally, the altered protein proportion was potentially attributed to the varied metabolism of yeast cells when grown in the different media [ 17 ], and the absence or presence of a certain compound in media would possibly lead to such an alteration in the resolution [ 18 ]. Although other ingredients in the cell wall could cause fluctuant resolution [ 19 ], further investigations are needed to determine the exact components that influence the cytometric resolution of the yeast cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as different gut microbial community was found in ASD patients in contrast to the healthy individuals, researchers attempted to modify the gut microbiome via probiotics and some results indicate bene cial effects on both behavioral and GI manifestations of ASD [46][47][48][49] . In addition, VPA rat model not just imitate ASD symptoms, it also has a transgenerational impact on the gut microbiota [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%